1993
DOI: 10.1002/cne.903270407
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of proneuropeptide Y‐derived peptides in the brain of Rana esculenta and Xenopus laevis

Abstract: The distribution of proneuropeptide Y-containing perikarya and nerve fibers in the brain of Rana esculenta and Xenopus laevis was determined with antisera directed toward neuropeptide Y and the carboxyl terminal flanking peptide. The distribution of proneuropeptide Y-like immunoreactivity was similar in both anurans. In the telencephalon, immunoreactive perikarya were found in the olfactory bulb, all subdivisions of the pallium, the septum, pars lateralis of the amygdala, the nucleus accumbens, and the anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 63 publications
2
23
0
Order By: Relevance
“…Also different in Dermophis is the lack of NPFF-ir cells in the caudal rhombencephalon, in contrast with the situation in anurans and urodeles where a conspicuous cell population is present in the nucleus of the solitary tract [Crespo et al, 2003]. Of note, a similar situation was found in the solitary tract attending to NPY-containing cells that are absent in gymnophionans [Ebersole et al, 2001] and present in anurans and urodeles [Perroteau et al, 1988;Lázár et al, 1993].…”
Section: Comparative Aspects Of Npff Immunoreactivitymentioning
confidence: 63%
“…Also different in Dermophis is the lack of NPFF-ir cells in the caudal rhombencephalon, in contrast with the situation in anurans and urodeles where a conspicuous cell population is present in the nucleus of the solitary tract [Crespo et al, 2003]. Of note, a similar situation was found in the solitary tract attending to NPY-containing cells that are absent in gymnophionans [Ebersole et al, 2001] and present in anurans and urodeles [Perroteau et al, 1988;Lázár et al, 1993].…”
Section: Comparative Aspects Of Npff Immunoreactivitymentioning
confidence: 63%
“…Conversely, in rat, the suprachiasmatic nucleus is devoid of hcrt-positive cell bodies and exhibits only very few hcrt-immunoreactive fibers Cutler et al, 1999). Likewise, it has been reported previously that the frog suprachiasmatic nucleus is enriched with NPY-positive cell bodies (Danger et al, 1985;Lázá r et al, 1993;Tuinhof et al, 1994), whereas the rat suprachiasmatic nucleus only contains NPY-positive processes (O'Donohue et al, 1985;DeQuidt and Emson, 1986). In the frog diencephalon, three other nuclei contained hcrt-positive neurons, i.e., the anterior preoptic area, and the magnocellular and ventral hypothalamic nuclei.…”
Section: Comparative Distribution Of Hcrt-related Peptides In the Cnsmentioning
confidence: 82%
“…In the inferior olivary complex of rat, both upregulation and down-regulation of NPY expression has been observed during development, and, in the adult, NPY immunoreactivity could be detected only in colchicinepretreated animals (Morara et al, 1997). An immunoreactivity-promoting effect of colchicine also has been noted in adult amphibians (Lázá r et al, 1993). Tuinhof et al (1994) also reported more intense staining in some larval nuclei than in adults.…”
Section: Development Of Npy-ir Populationsmentioning
confidence: 85%